Ta‘limda fanlararo integratsiyani ta‘minlashda innovatsion ta‘lim texnologiyalardan foydalanish - Zaripova, D.A (SCIENCE and SOCIETY, 2023)
This article presents the effectiveness of the teaching methodology using innovative educational technologies in providing interdisciplinary integration of education.
Keywords: educational reforms; innovative teaching; active learning; innovative activities; e-learning; computer-assisted teaching; smart technologies